SOLVING PROBLEMS USING THE METHOD OF COORDINATES - N. Y. Toshboeva (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents the solution of algebraic and geometric problems with the method of coordinates. Here, there is a scientific substantiation of the convenience of solving problems with the method of coordinates, when the complexity of solving problems in the algebraic method arises.